N.P. VAN WYK LOUW AS SATIRIKUS - HP van Coller (Acta Theologica)
Critics usually try to discern the crucial tenets or themes in a major poet’s work. This is also the case in the reception of the famous Afrikaans poet, N.P. van Wyk Louw’s oeuvre, especially after the publication of Tristia (1962), often regarded as his magnum opus. In this article, the hypothesis is that many literary devices, which critics in the past have discerned in his work, all fall within the ambit of the satirical mode. The definition of satire proposed in this article is that satire is an implied or explicit attack on a satirical object, but also with the suggestion at least of an explicit satirical norm. In conclusion, two seminal poems by Van Wyk Louw that were, in the past, read as detached and reflective are interpreted as satirical, with reference to Speech Act Theory.